A house party in Tuscany : recipes, stories and art from Arniano - Guinness, Amber (Thames & Hudson Inc., 2022)
"Showcasing inviting and lush photography of the farmhouse's interiors and exteriors alongside mouthwatering images of simple and flavorful dishes, A House Party in Tuscany collects recipes from 30 years of cooking and hosting at Arniano, exemplifying fundamental principles of Italian home cooking. With essential ingredients for an Italian pantry; feast curation; menu suggestions for every season; notes on Italian wines; day trips from Arniano; tricks and rules for cooking that can be applied to any lunch or dinner party, whatever the season; guidelines to seemingly effortless cooking and hosting, this is a book to make everyone feel welcome" --